“Teaching culture based lessons in an online efl class at the Technical University of Cotopaxi” - Amancha Zamora, Tamara Nathaly (2022)
Teaching culture in foreign language classes is essential for students to develop their intercultural communicative competence. This qualitative case study aims to explore experiences of the implementation of culture-based lessons through authentic material and group discussion strategies in an EFL class at the Technical University of Cotopaxi. The analyzed data were collected over the implementation of online culture-based lessons by an English professor during an academic term in a class of 37 students, which was observed by 2 peer teachers. The students’ answers were examined from an open-ended survey, cultural journals, and teacher and peer teachers’ reflections. This study shows that for teaching culture in English classes, the professor had to bear in mind some pedagogical considerations related to authentic material, comparison of mother and target culture, previous vocabulary and cultural awareness, e-learning tools, enough time for activities completion, strategies for discussions, and diversity of students in a class. In addition, the improvement of cultural knowledge, peer interaction/learning, and students’ communicative competence were advantages resulting from the cultural classes and discussions. Nevertheless, during the teaching-learning culture, difficulty was faced in finding short authentic videos, creating class activities, finding English videos on L1, time management, students’ participation, lack of cultural and vocabulary knowledge in group discussions, and technological problems. Finally, the lessons taught had a positive impact on the students’ cultural learning and their ICC. Based on these findings, it is suggested to increase the teaching of the target language culture to strengthen the learners’ cultural awareness and communication skills.